Monetary and fiscal policy. - Persson, Torsten; Tabellini, Guido Enrico, 1956- (MIT Press, 1994)
How will the private sector react to different government policies? What policies will produce the most desirable outcomes? The two volumes of Monetary and Fiscal Policy bring together major contributions to a new theory of macroeconomic policy that analyzes which policies are credible or politically feasible -- topics that are central to the practical policy debate but that traditional theory cannot address. This volume examines problems of policy credibility caused by incentives to deviate from announced policy.